The genome sequences of Arachis duranensis and Arachis ipaensis, the diploid ancestors of cultivated peanut - Bertioli, D.J.; Cannon, Steven B.; Froenicke, L.; Huang, G.; Farmer, Andrew D.; Cannon, Ethalinda K.S.; Liu, X.; Gao, D.; Clevenger, J.; Dash, S.; Ren, L.; Moretzsohn, K.; et al. (Springer, 2016)
David Bertioli and colleagues report the genomes of Arachis duranensis and Arachis ipaensis, the diploid ancestors of cultivated peanut, Arachis hypogaea. Their analyses are a first step in understanding the evolution of the peanut's tetraploid genome. Cultivated peanut (Arachis hypogaea) is an allotetraploid with closely related subgenomes of a total size of ∼2.7 Gb. This makes the assembly of chromosomal pseudomolecules very challenging. As a foundation to understanding the genome of cultivated peanut, we report the genome sequences of its diploid ancestors (Arachis duranensis and Arachis ipaensis). We show that these genomes are similar to cultivated peanut's A and B subgenomes and use them to identify candidate disease resistance genes, to guide tetraploid transcript assemblies and to detect genetic exchange between cultivated peanut's subgenomes. On the basis of remarkably high DNA identity of the A. ipaensis genome and the B subgenome of cultivated peanut and biogeographic evidence, we conclude that A. ipaensis may be a direct descendant of the same population that contributed the B subgenome to cultivated peanut.